Cholecalciferol vs. Small Doses of Alfacalcidol vs. Placebo in Chronic Kidney Disease Patients on Hemodialysis: A Randomized Parallel Group Study - Matuszkiewicz-Rowińska, Joanna; Kulicki, Paweł; Zebrowski, Paweł; Klatko, Wiesław; Sokalski, Antoni; Niemczyk, Stanisław; Wypych-Birecka, Magdalena; Małyszko, Jolanta (Frontiers in Medicine, 2022)
Background The ability of extrarenal tissues to convert 25(OH)D (calcidiol) into 1,25(OH)2D (calcitriol) and dependence of the conversion on substrate levels provide the rationale for supplementing vitamin D in dialysis patients who usually have severe depletion of both: 25(OH)D and 1,25(OH)2D. The primary aim of the study was to compare effects of small doses of cholecalciferol (12,000 IU/week) with frequently used in Europe, small doses of alfacalcidol (1.5 μg/week) or placebo, given for 12 weeks, on serum 1,25(OH)2D in hemodialysis patients with 25(OH)D deficiency. Secondary outcomes were changes in serum calcium, phosphate, 25(OH)D, parathyroid hormone (PTH), fibroblast growth factor 23 (FGF23) and sclerostin during the treatment. Methods This was a prospective, randomized, partly double-blind (cholecalciferol vs. placebo) study. Out of 522 patients dialyzed in 5 centers in the Mazovian Province, 93 gave informed consent and met the inclusion criteria: any vitamin D metabolites and calcimimetics naïve; no history of liver or intestinal disease; serum 25(OH)D <20 ng/ml, iPTH <1,000 –>110 pg/ml, calcium <10.2, and phosphate <6.8 mg/dl. The subjects were stratified by serum iPTH, then randomized into 3 groups according to the treatment. Results To our knowledge, this is the first study comparing head-to-head these drugs in the hemodialysis population. There were no significant differences between the groups at baseline. 81 patients completed the study. Cholecalciferol normalized serum 25(OH)D, with a mean rise from 12.9 ± 6.7 to 31.3 ± 10.1 ng/ml (p < 0.0001). This was accompanied by a marked increase of 1,25(OH)2D from 13.8 ± 9.3 to 25.1 ± 14.2 pmol/l (p < 0.0001). A rise in serum 1,25(OH)2D was also observed in alfacalcidol treated patients, however much smaller (from 13.5 ± 10.1 to 18.5 ± 11.0 pmol/l; p = 0.02). Neither cholecalciferol nor alfacalcidol treatment resulted in significant changes in serum PTH and the remaining parameters. Conclusions In most patients, treatment with cholecalciferol in a 12,000 IU/week dose permits safe correction of 25(OH)D deficiency and is more effective than 1.5 μg/week dose of alfacalcidol in rising serum 1,25(OH)2D. This, together with a lack of influence on circulating iPTH the usefulness of such small alfacalcidol doses in hemodialysis patients is debatable.